Antioxidant Activity of the Extracts Derived from Terminalia catappa: Antioxidant Activity of Terminalia catappa (Biological Sciences - PJSIR, 2011)
The extracts derived from Terminalia catappa leaves and fruit following antioxidant activity directed isolation, were screened for their antioxidant activity through their ability to scavenge DPPH radicals. Only fractions which exhibited >50% DPPH scavenging effect at each step of isolation were selected for further purification and judge their ability to reduce peroxide formation (peroxide value) in heated corn oil. The results indicated that crude ethanolic extract, aqueous fraction of crude extract and its sub fractions (petroleum ether and ethylacetate) possessed prominent antioxidant activity. In addition, phytochemical analysis showed that the five fractions obtained finally contain simple phenols, anthocyanins, phenyl propanoids and flavanols.